Phylogenetic analysis of Alexandrium species and Pyrodinium bahamense (Dinophyceae) based on theca morphology and nuclear ribosomal gene sequence) - Chui, P.L; Po, T.L; Boon, K.N; Mei, Y.C; Ahmad, A.; Usup, G. (Phycologia, 2005)
A phylogenetic analysis of Alexandrium species and Pyrodinium bahamense was carried out. The analysis was based on nucleotide sequences of the large subunit ribosomal RNA gene and 16 morphological characters considered taxonomically informative. Maximum likelihood, maximum parsimony and Bayesian approaches were used. Molecular and morphological data were analysed independently and in combination. The outcomes of all the analyses were the same. Pyrodinium was consistently grouped in the same clade with Alexandrium, specifically with the subgenus Gessnerium, A. pseudogoniaulax and A. taylori. Two monophyletic clades were resolved. The first comprised A. tamarense, A. fundyense, A. catenella, A. tamiyavanichii, A. affine and A. concavum, with the base formed by A. pseudogoniaulax, A. taylori and P. bahamense. The second clade comprised the species A. minutum, A. insuetum, A. tamutum, A. andersoni, A. ostenfeldii and A. leei, with A. margalefi forming the base. Mapping of morphological characters onto the phylogenetic trees indicated that posterior sulcal plate probably has the highest value in the taxonomy of Alexandrium. Some other characters considered taxonomically important, such as the ventral pore and position of the anterior attachment pore, are most probably homoplastic.